Potensi Bioremediasi Minyak Diesel dengan Menggunakan Bakteri Bacillus subtilis: Kajian Literatur - Aghniya Nur Rizka Fadila; Muhammad Rafi Pratama Shidiq; Triani Nur Fitri (Jurnal Biodiversitas dan Bioteknologi, 2025)
Diesel is a pollutant fossil fuel that is used significantly. Its carcinogenic nature is a by-product of petroleum processing, if diesel spills or pollutants are diluted, it will have a dangerous environmental lethal effect. Bacillus subtilis is a hydrocarbonoclastic bacterium capable of secreting hydroxylase enzymes, which can degrade hydrocarbons and their derivatives into simpler compounds. So the purpose of this literature review is to determine the potential effectiveness of B. subtilis bacteria in bioremediating Diesel Oil. The method used is a literature review sourced from official websites and the like. Bacteria B. subtilis has the ability to remediate diesel with enzymes produced, suitable bioremediation techniques namely bioaccumulation, biostimulation, and bioavability that meet the success factors. The results showed that B. subtilis was able to degrade diesel to 12.8% diesel content within 12 days. With this ability, this bacterium is a bioremidiation agent that can be used to remediate diesel.